Pelatihan Pelatihan Pembuatan Handsanitizer dan Pembagian ‘Siaga Kit’ Sebagai Upaya Pencegahan Covid-19 Di Lamongan - Utami, Primanitha Ria; Devi Ristian Octavia (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
COVID-19 can occur at any ages, so it requires awareness to break the chain of this infection,including:Social Distancing, hand hygiene, wearing masks, and consuming multivitamins as needed. This activity on March 2020.There are still many people who have low awareness like do not wear masks when they leave the house.Therefore, our team made a hand sanitizer based on the WHO formula and distributed a 'siaga kit' to residents of the Lamongan community as a form of concern for COVID-19. Our team consists of Pharmacy lecturers, Laboratory Assistants and Pharmacy students at the Muhammadiyah University of Lamongan. Students are given education about the objectives and procedures for making handsanitizers. Furthermore, students' knowledge and understanding about making Handsanitizer was measured by giving a questionnaire to evaluate the knowledge of Handsanitizer making. The result of the handsanitizer making training was that students had a good understanding of the procedures for making handsanitizers. The activity of distributing 'siaga kit' to the Lamongan community also received a very good response.